2014
DOI: 10.1002/chem.201404809
|View full text |Cite
|
Sign up to set email alerts
|

Lutetium‐Methanediide‐Alkyl Complexes: Synthesis and Chemistry

Abstract: The first four-coordinate methanediide/alkyl lutetium complex (BODDI)Lu2 (CH2 SiMe3 )2 (μ2 -CHSiMe3 )(THF)2 (BODDI=ArNC(Me)CHCOCHC(Me)NAr, Ar=2,6-iPr2 C6 H3 ) (1) was synthesized by a thermolysis methodology through α-H abstraction from a Lu-CH2 SiMe3 group. Complex 1 reacted with equimolar 2,6-iPrC6 H3 NH2 and Ph2 C+O to give the corresponding lutetium bridging imido and oxo complexes (BODDI)Lu2 (CH2 SiMe3 )2 (μ2 -N-2,6-iPr2 C6 H3 )(THF)2 (2) and (BODDI)Lu2 (CH2 SiMe3 )2 (μ2 -O)(THF)2 (3). Treatment of 3 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…An X‐ray diffraction study illustrated that the insertion reaction of two equivalents of CyN=C=NCy into Lu‐µ 2 ‐CHSiMe 3 bond of 1 led to a cascade reaction containing Si‐C bond cleavage, SiMe 3 migration and Si‐N bond formation . This result is similar to that observed in the reaction of complex 1 with two equivalents of phenyl isocyanate . Unexpectedly, the C–H bond of pyridine was activated by Lu‐CH 2 SiMe 3 to form the Lu‐ o ‐pyridine bond, which further inserted into another CyN=C=NCy molecule (Scheme ).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…An X‐ray diffraction study illustrated that the insertion reaction of two equivalents of CyN=C=NCy into Lu‐µ 2 ‐CHSiMe 3 bond of 1 led to a cascade reaction containing Si‐C bond cleavage, SiMe 3 migration and Si‐N bond formation . This result is similar to that observed in the reaction of complex 1 with two equivalents of phenyl isocyanate . Unexpectedly, the C–H bond of pyridine was activated by Lu‐CH 2 SiMe 3 to form the Lu‐ o ‐pyridine bond, which further inserted into another CyN=C=NCy molecule (Scheme ).…”
Section: Resultssupporting
confidence: 64%
“…The alkyl protons of the two LuCH 2 SiMe 3 species show an AB spin system at –0.40 and –0.34 ppm correlating with a broad carbon signal at 42.50 ppm. The singlet signal at 0.92 ppm in the 1 H NMR spectrum and 117.16 ppm in the 13 C NMR spectrum can be assigned to the newly generated methanediide unit Lu‐µ 2 ‐CHSiMe 3 , very close to that of complex 1 …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…[3] Notwithstanding, such bridging alkylidenem oieties were accessed in mixed methyl/methylidene, [4] methyl/chloride, [5] cubane-like methylidene complexes, [6] and the first four-coordinate methandiide alkyl lutetium complex. [7] Also, Lewis acid-stabilized [8] or pincerlike rare-earth-metal alkylidenec omplexes [9] have been reported. Recent advances in the latter areas are represented by the syntheses of the first bridged bis-alkylidene scandium complex, [10] an on-pincer-type monometallic phosphinoalkylidene scandium complex, [11] and silyl-thiophosphinoyl alkylidene as well as phosphinomethylidener are-earth-metal compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Some pincer-like rare-earth alkylidene complexes have been reported independently by Cavell, 4 Liddle, 5 and Mézailles. 6 Very recently, Cui et al reported the lutetium methanediide-alkyl complexes, 7 and Chen et al reported the non-pincer-type mononuclear scandium alkylidene complexes. 8 Furthermore, rare-earth methylidene complexes were also stabilized by chloride bridges 9 or Lewis-acids such as AlMe 3 .…”
mentioning
confidence: 99%